أوجه التناسب المقاصدي بين سورة الحديد مع سورة المجادلة - العليمي، راشد سعد (جامعة الإمام محمد بن سعود الإسلامية - الجمعية العلمية السعودية للقرآن الكريم وعلومه, 2023)
تم في هذا البحث الذي حمل عنوان: "من أوجه التناسب المقاصدي بين سورة الحديد مع سورة المجادلة"، توضيحا للعلاقة بين سورتين متتابعتين في القرآن الكريم، وفيهما المعاني المترابطة حول مقصد واحد ألا وهو علم الله سبحانه، من الجهة التقريرية، ومن ثم الواقعية في حياة الفرد والمجتمع. وحرصت على اختيار هذا الموضوع لأهميته في التعرف على إعجاز القرآن الكريم، وأيضا على ترابط سوره في نسق حكيم مبارك، ومن بعد هذا يكون التعرف على هذا العلم سبيلا في سهولة بلوغ التفسير ولفهم المراد في السورة. واخترت دراسة الارتباط والمناسبة بين سورة الحديد وسورة المجادلة، لتتابعهما في القرآن، ولوجود ارتباط عظيم وواضح ذكرته في هذا البحث. In this research, which was titled: "From the aspects of proportionality between Surat Al-Hadid with Surat Al-Mujadila," an explanation and study of the relationship and proportionality between two successive Surahs in the Holy Qur'an, and in an effort to clarify the meanings that are interrelated between them around one goal, which is the attribute of God's knowledge, from the corresponding declarative point of view., and then realism in the life of the individual and society. I was keen to choose this topic because of its importance in identifying the miracles of the Noble Qur'an, and also on the interrelation of its surahs in the pattern of a wise and blessed one. I chose to study the link and the occasion between Surat Al-Hadid and Surat Al-Mujadila, because of their succession in the Qur'an, and because there is a great and clear link that I mentioned in this research.
Keywords: القرآن الكريم -- تفسير السور القرآنية -- علم ترابط السور -- علم المناسبات